Nayan Parikh & Consultants : loan against shares - Varma, Jayanth, (SAGE Business cases., 2024)
Nayan Parikh, CEO of Nayan Parikh & Consultants (NPC), had to decide on the course of action for recovering a loan extended to Shrenikbhai Vimawala, Chairman and Managing Director of Shrenik Limited, against a pledge of Shrenik shares. Almost a year had passed since the three-month loan was disbursed. NPC had provided multiple extensions of time to Vimawala taking into account the disruption caused by the Covid-19 pandemic. The loan to Vimawala was the first loan that NPC had granted on the security of shares. Most of its lending activities in the past had been against real estate. Therefore, Parikh was also keen to review the entire transaction carefully and determine what lessons he could draw about loan against shares as a possible future line of business for NPC.